PROSECUTION OF MONEY LAUNDERING OF PROCEEDS OF CORRUPTION BY ANTI-CORRUPTION COMMISSION (KPK) - Muh. Fatahillah Akbar (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractAs extra ordinary crime, corruption which may be done in several ways is hard to be eradicated. One of the ways is money laundering. The problem which arises is that KPK has no authority to prosecute money laundering of corruption proceed. This research aims to explore the authority to prosecute money laundering of corruption proceed based on existing legislations and to also provide the reform of law regarding to that issue. The research shows that there is no regulation which authorizes KPK to prosecute money laundering. To cope with that problem, the reform of laws is necessary by: First, combining the regulation of money laundering and corruption in one legislation; and Second, authorizing KPK to prosecute money laundering of corruption proceed by putting the authority in a legislation.IntisariSebagai extra ordinary crime, korupsi dengan berbagai modus operandi tidak mudah diberantas. Salah satu modus operandi yang kompleks adalah TPPU. Permasalahan yang timbul dalam TPPU hasil tindak pidana korupsi adalah dimana KPK tidak diberikan kewenangan melakukan penuntutan terhadap TPPU hasil korupsi. Penelitian ini bertujuan untuk mengeksplorasi kewenangan penuntutan terhadap perkara TPPU hasil korupsi dalam hukum positif dan memberikan reformulasi pengaturan terhadap hal tersebut. Hasil penelitian menunjukan bahwa terdapat kekosongan hukum dalam penegakan hukum pada perkara TPPU hasil tindak pidana korupsi yang ditangani KPK. Untuk mengatasi permasalahan tersebut perlu reformulasi peraturan dengan: (1) mengatur secara tersendiri TPPU dalam UU PTPK; dan (2) memberikan kewenangan KPK untuk melakukan penuntutan terhadap perkara TPPU hasil tindak pidana korupsi.